INTERNASIONALISASI POTENSI SULAWESI BARAT (Studi Kasus: Investasi Asing di Sulawesi Barat) - Badu, Muhammad Nasir (JPP (Jurnal Politik Profetik), 2014)
This research is aimed at observing the efforts of West Sulawesi government to sell its local potentials to international markets. To achieve this aim, this research applies qualitative descriptive analysis by studying cases of foreign investments to gather detailed empirical data of reseach analysis units. The data are collected through libarary visit, interviews and observation to obtain both primary and secondary ones. The result shows that the efforts of West Sulawesi government to sell its local potentials are still less even though the opportunities to attract foreign investments are largely available. In order to overcome this issue, there should be a synergic effort to minimize possible heavy challenges. Keywords: Internasionalisasi, Intervensi Asing, dan Sulawesi Barat